Susceptibility of Austrian Clinical Klebsiella and Enterobacter Isolates Linked to Patient-Related Data - Badura, Alexandra; Pregartner, Gudrun; Holzer, Judith C.; Feierl, Gebhard; Grisold, Andrea J. (Frontiers in Microbiology, 2016)
The aim of the study was to analyze the antimicrobial susceptibility of Austrian clinical Klebsiella spp. and Enterobacter spp. isolates linked to patient-related data over a time period from 1998 to 2014. The main findings of this study were (i) a marked difference of antibiotic susceptibility rates between different infection sites for both Klebsiella spp. and Enterobacter spp., (ii) significantly greater percentages of resistant isolates among both Klebsiella spp. and Enterobacter spp. in male patients compared to female patients and (iii) significantly greater percentages of resistant isolates among both Klebsiella spp. and Enterobacter spp. from hospital-derived samples compared to samples from the community. In conclusion, our statistical data analysis clearly indicated a strong association of patient-related data and Klebsiella spp. and Enterobacter spp. susceptibility profiles.